A review of the effectiveness of chlorogenic acid in green coffee for human health: Article review - Aliyah Fahmi; Epi Supri Wardi (International Journal of Nursing and Midwifery Research, 2026)
Chlorogenic acid (CGA) is a polyphenolic compound produced in certain plants, one of which is coffee. Green coffee has a higher CGA number than other types of coffee of the same weight. CGA is a compound that has been shown to be the main component of green coffee. The benefits of CGA as a healthy ingredient have been demonstrated in many studies. This review describes the effectiveness of green coffee CGA in reducing the number of illnesses that are dangerous to human health. In related literature, the effects of CGA have been reported in vitro, in vivo, and in clinical trials. CGA research in clinical trials is primarily focused on its antioxidant activity, human oxidative response, and the best results as an antioxidant. In this study, you will learn about the CGA stability and health tolerance of green coffee. We will also learn about the effectiveness of CGA for many aspects of its health effects by reviewing recent studies as our intent.